Meaning of “Taboo Association” in Bugis Community of Tanah Pilih Village, Banyuasin, South Sumatra - Margareta Andriani; Hastari Mayrita; Venti Deviana (GoAcademica Research & Publishing, 2023)
This study examines the importance of taboo meaning in the Bugis community in Tanah Pilih Village, Banyuasin Regency, South Sumatra. The purpose of this study is to describe the importance of the meaning of taboo associations in the Bugis community of Tanah Pilih Village, Banyuasin Regency. The method used in this study is a qualitative method, ethnographic approach. Data was collected from six informants. Data collection techniques used include interviews, observation, recording, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The subjects of this study were individuals who had a deep understanding of taboos in the village of Tanah Pilih. The results of the study revealed fifteen taboo association meanings. Of the six informants, five members of the spark plug community still believed in and adhered to the taboos, while one informant did not believe in the taboos. Taboos are meant to be associated with the goal of educating children, ensuring that their behavior and attitudes remain appropriate, and promoting the ethical values ​​of respect and decency. Tabu is the first choice of Bugis parents to proactively combat the negative effects of globalization on their children.